2022
DOI: 10.1038/s41598-022-05821-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between capillary glucose during pregnancy and childhood growth to the age of five: a cohort study

Abstract: The objective of this study was to evaluate the relationship between random capillary glucose levels in healthy pregnant women and infant size at birth and childhood growth to the age of five years. This population-based cohort study comprised 10,937 healthy mother–child dyads. Data on highest maternal random capillary glucose level during pregnancy and sequential anthropometric data on their children during the first five years of life were gathered from the Uppsala County Mother and Child Cohort. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This has been reported in infants born to mother with higher maternal glucose levels who had a higher birth weight, followed by a period of slower growth in infancy, compared to infants of mothers with lower glucose levels 14 . Similar results were found in a population study, where random capillary glucose was performed in healthy pregnant women and a positive relationship between elevated glucose and birth weight was reported, with subsequent decreased childhood growth velocity up to age five 15 . Furthermore, Titmuss et al 57 found children exposed to hyperglycaemia in utero compared to unexposed children had lower weight, length/height and BMI trajectories in infancy followed by a similar weight and BMI at completion of the study at age three.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This has been reported in infants born to mother with higher maternal glucose levels who had a higher birth weight, followed by a period of slower growth in infancy, compared to infants of mothers with lower glucose levels 14 . Similar results were found in a population study, where random capillary glucose was performed in healthy pregnant women and a positive relationship between elevated glucose and birth weight was reported, with subsequent decreased childhood growth velocity up to age five 15 . Furthermore, Titmuss et al 57 found children exposed to hyperglycaemia in utero compared to unexposed children had lower weight, length/height and BMI trajectories in infancy followed by a similar weight and BMI at completion of the study at age three.…”
Section: Discussionsupporting
confidence: 84%
“… 14 Similar results were found in a population study, where random capillary glucose was performed in healthy pregnant women and a positive relationship between elevated glucose and birth weight was reported, with subsequent decreased childhood growth velocity up to age five. 15 Furthermore, Titmuss et al 57 found children exposed to hyperglycaemia in utero compared to unexposed children had lower weight, length/height and BMI trajectories in infancy followed by a similar weight and BMI at completion of the study at age three. While we did not find that elevated maternal glucose was associated with a slowing of postnatal growth or “catch down”, this may reflect the study population presented here as the aforementioned study consisted of women with a BMI in the normal range and almost half of women were in their first pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial studies have shown that higher gestational blood glucose, whether in fasting or postprandial states in each trimester, is associated with an increased risk of adverse birth outcomes, even in nondiabetic pregnancies [11]. Indeed, higher random glucose levels in healthy pregnant women are associated with larger babies at birth and lower growth velocity in early childhood [12]. Hyperglycemia also contributes to childhood obesity, cardio metabolic disorders in women and growing long-term burden on future generations [13].…”
Section: Introductionmentioning
confidence: 99%